2019
DOI: 10.3892/etm.2019.7172
|View full text |Cite
|
Sign up to set email alerts
|

B‑cell activating factor receptor expression is associated with germinal center B‑cell maintenance

Abstract: B-cell activating factor (BAFF) is a major cytokine that regulates B-cell survival, maturation and differentiation through its binding with its receptors: BAFF receptor (BAFF-R), transmembrane activator and cyclophilin ligand interactor (TACI) and B-cell maturation antigen (BCMA). These receptors have been demonstrated to be involved in tertiary lymphoid structure formation; however, their role in germinal centers (GCs) has remained elusive. The aim of the present study was to determine the expression profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…However, direct evidence to support BAFF expression by FDCs was lacking and solely based on imaging of the follicle and qPCR of impure cell suspensions ( Hase et al, 2004 ). A recent study showed the BAFF protein to be present in all regions of the follicle, with the highest concentration in the mantle zone, a region where MRCs reside ( Carrillo-Ballesteros et al, 2019 ). This is consistent with our expression data, and together with recent literature, this supports an outward-in gradient instead of an inward-out gradient of BAFF in the follicles, designating MRCs and not FDCs as the major BAFF producers.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct evidence to support BAFF expression by FDCs was lacking and solely based on imaging of the follicle and qPCR of impure cell suspensions ( Hase et al, 2004 ). A recent study showed the BAFF protein to be present in all regions of the follicle, with the highest concentration in the mantle zone, a region where MRCs reside ( Carrillo-Ballesteros et al, 2019 ). This is consistent with our expression data, and together with recent literature, this supports an outward-in gradient instead of an inward-out gradient of BAFF in the follicles, designating MRCs and not FDCs as the major BAFF producers.…”
Section: Discussionmentioning
confidence: 99%
“…BAFF, a member of the tumor necrosis factor family, is mainly expressed by immune cells such as monocytes, macrophages, neutrophilic granulocytes, and dendritic cells 25 . Thus, equal amounts of thyroid MCs from each sample were randomly divided into control (0 pmol/L), no‐target control siRNA (Nsi), BAFF siRNA (Bsi), T3 (10 6 pmol/L), T3 (10 6 pmol/L) + no‐target control siRNA (T3 + Nsi), and T3 (10 6 pmol/L) + BAFF siRNA (T3 + Bsi) groups for co‐culture.…”
Section: Resultsmentioning
confidence: 99%
“…27 Other studies have shown that GC B cells and memory B cells express BCMA, and this receptor regulates the generation of B cell responses. 17,28 In lupus prone mice, BCMA deficiency leads to elevated autoantibody responses and increased morbidity and mortality demonstrating that BCMA regulates autoreactive B cell responses. 22 Recent studies suggested that BAFF and APRIL have functional effects on non-B-lineage cell types including myeloid Figure 6 BAFF and APRIL Signals Through BCMA to Have Proinflammatory Functions in Myeloid Cells CD11b + myeloid cells were MACS sorted from healthy (A) BCMA +/+ and (B) BCMA −/− mice and stimulated with lipopolysaccharides in the presence or absence of BAFF or APRIL (n = 3/group).…”
Section: Discussionmentioning
confidence: 99%
“…However, BAFF and APRIL also have effects on B cells at later stages of maturation and on non-B cells, which may also affect EAE. [17][18][19] Unlike BAFFR deficiency, BCMA-deficient mice have no overt defects in the development and homeostasis of B cell populations, although it has been reported that there are effects on antigen presentation and the maintenance of longlived plasma cells. 20,21 Previous studies have identified that BCMA has regulatory properties on inflammation in mouse models of lupus, where BCMA deficiency exacerbates lupuslike disease activity in mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation